2021
DOI: 10.1093/ecco-jcc/jjab012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Ozanimod in Moderately to Severely Active Ulcerative Colitis: Results From the Open-Label Extension of the Randomized, Phase 2 TOUCHSTONE Study

Abstract: Background and Aims This analysis examined the long-term safety and efficacy of ozanimod in patients with moderately to severely active ulcerative colitis [UC] with ≥ 4 years of follow-up in the phase 2 TOUCHSTONE open-label extension [OLE]. Methods Patients receiving placebo or ozanimod HCl 0.5 mg or 1 mg during the double-blind period could enter the OLE [ozanimod HCl 1 mg daily]. Partial Mayo score [pMS] clinical response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 31 publications
0
46
0
4
Order By: Relevance
“…Ozanimod 0.5 mg did not show a statistically significant benefit. An open-label extension study, 55 with all patients treated with ozanimod 1 mg/d, showed rapid improvement in Mayo scores for patients who switched from the placebo or ozanimod 0.5 mg/d. Long-term benefit with ozanimod 1 mg daily was displayed in patients with moderate-to-severe ulcerative colitis both on clinical and histologic measures.…”
Section: Ozanimod For the Treatment Of Other Immune-mediated Diseasesmentioning
confidence: 99%
“…Ozanimod 0.5 mg did not show a statistically significant benefit. An open-label extension study, 55 with all patients treated with ozanimod 1 mg/d, showed rapid improvement in Mayo scores for patients who switched from the placebo or ozanimod 0.5 mg/d. Long-term benefit with ozanimod 1 mg daily was displayed in patients with moderate-to-severe ulcerative colitis both on clinical and histologic measures.…”
Section: Ozanimod For the Treatment Of Other Immune-mediated Diseasesmentioning
confidence: 99%
“…Fingolimod (FTY720), an agonist for S1PRs (S1PR1, S1PR3, S1PR4, and S1PR5), has been approved for multiple sclerosis (MS) by the FDA, showing anti-tumor effects in CRC mouse models [ 30 ]. Ongoing clinical trials (TOUCHSTONE study) also claimed that ozanimod, a highly selective agonist for S1PR1 and S1PR5, showed favorable therapeutic effectiveness for ulcerative colitis (NCT01647516, NCT02531126) [ 177 , 178 ]. It is well established that patients with long-standing ulcerative colitis can develop CRC [ 81 ].…”
Section: Targeting Gpcrs In Gi Cancer Therapymentioning
confidence: 99%
“…Ozanimod has been shown to reduce inflammation and disease parameters in three models of autoimmune disease, including colitis [136]. The results of open-label extension (OLE) of the TOUCHSTONE clinical trial in patients with moderate to severe ulcerative colitis demonstrated that ozanimod has significant benefits and long-term efficacy based on clinical, endoscopic and biomarker measures for up to 4 years of treatment [147]. Endoscopic, histological and clinical improvement was also observed within 12 weeks after initiation of ozanimod in STEPSTONE clinical trial in patients with moderately to severely active Crohn's disease [148].…”
Section: Additional Effects Under Investigationmentioning
confidence: 99%